Tinjauan Yuridis Perlindungan Hukum Terhadap Penggunaan Dompet Digital (E-Wallet) Dalam Sistem Pembayaran Di Indonesia - Nur Hidayah; Asbullah (PT PUSTAKA CENDEKIA GROUP, 2024)
This research aims to determine the form of use of Digital Wallets in the payment system in Indonesia and to determine legal protection for the use of digital wallets in Indonesia. This research uses normative legal research methods. The use of normative research methods in research efforts and writing this article is based on the suitability of theory with the research methods required by the author. 1) Electronic Wallet Operators provide services in the form of online transaction payments so that the process becomes more practical, faster and cheaper. Electronic Wallets are equipped with various features to facilitate online transactions between consumers and business owners or between business actors (B2B). In the mechanism, the Electronic Wallet will be filled in by consumers (deposits) via their banking account with the desired nominal value. Then, if the consumer makes a transaction, the Electronic Wallet will be debited according to the nominal transaction. When making a deposit, this Electronic Wallet can be filled via several payment methods, namely via credit card, mobile banking, internet banking, ATM, debit card, corporate internet banking, branchless banking agent, online virtual account, and Electronic Invoice Presentment & Payment ( EIPP ). and 2) Dana e-wallet users who suffer losses due to non-compliance with the services they receive can take out loans for their losses legally through court or outside court in accordance with the provisions of the Consumer Protection Law.